Una Nueva Forma de Reducir la Intermitencia Eléctrica de Manera Sustentable, Caso de Estudio: Un Sistema Híbrido Tipo Rebombeo Solar en México - Ramos, Leonardo de Jesus; Fragoso, Manuel Montenegro (Ingeniería, 2019)
Context: Mexico before 2013, had a unilateral government-like control of the electricity sector, a situation that was modified with the energy reform, where the operating policies changed, creating a new scheme based on a Wholesale Electricity Market (MEM) through an open market and where the sources with the greatest presence to date are intermittent power generation sources, such as; photovoltaic solar power plants and wind power plants. The intermittency of these sources arising in the electrical transmission network will cause a problem of energy security called the duck curve. Method: This technical-administrative study makes a detailed panorama to structure a model through decision making with the Hierarchical Analysis Process (AHP, acronym in English) to repower the Mexican electric sector by making decisions with social criteria, environmental, economic, political and technical. Results: A sensitivity analysis is presented as a result of the LINGO Software and Web Hipre that supports the criterion and sub-criterion that will benefit the most by including a new innovation called Re-pumping-solar to save-the public finances and decrease the electrical intermittency in Mexico. Conclusions: Lead to decision making, technologies within energy policies without the need for a physical model, but yes; with an investigation of operations verifying the feasibility of said technologies.